Protective effects of paeonol on cardiovascular complications in diabetes mellitus involves modulation of PI3K /Akt-GSK-3β signalling, regulation of protease-activated receptor-1 expressions and down-regulation of inflammatory mediators - Li, Jun; Xu, Ze-Qing; Bao, Ling; Li, Zhi-Cao; Qu, Jia-Xiang (Bangladesh Journal of Pharmacology, 2015)
The present study was taken as an effort to assess the effects of paeonol on diabetic cardiomyopathy. Diabetes was induced in separate groups of Sprague-Dawley rats using streptozotocin. Treatment group animals received paeonol (50, 100 or 200 mg/kg body weight/day; orally) 5 weeks after streptozotocin induction for 6 weeks. Paeonol strikingly reduced myocardial apoptosis and improved cardiac function and myocardial architecture. Serum levels of glucose, reactive oxygen species and inflammatory mediators (TNF-α, IL-6 and IL-1β) were significantly reduced with decreased accumulation of collagen in the cardiac tissue. Paeonol modulated p-Akt, glycogen synthase kinase-3β and glycogen synthase, while significantly down-regulated protease-activated receptor-1, caspase-3, TNF-α, NF-κB p65, and p-Iκ-Bα expressions. Paeonol effectively suppressed diabetic cardiomyopathy by improving myocardial function, regulating the inflammatory responses and Akt signalling.